EU Fair of European Innovators in Cultural Heritage - Ioannides, Marinos (My University, 2026)
Organised by the European Commission as a key event of 2018 European Year of Cultural Heritage, the 'Fair of European Innovators in Cultural Heritage' took place on 15-16 November 2018 in Brussels.
Keywords: Sciences